Optimization of particle rinsing process in linker-free post-synthesis functionalization for sensitive encoded hydrogel microparticle-based immunoassay - Bae, Su Hyeon; Jang, Wookyoung; Choi, Jun Hee; Mun, Seok Joon; Bong, Ki Wan (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
Graphically encoded hydrogel microparticles has garnered attention as effective multiplex immunoassay platform owing to their large multiplex capacity and high sensitivity. In particular, the newly developed capture antibody functionalization technique for hydrogel microparticle-based immunoassay called linker-free post-synthesis functionalization (PSF) enables enhanced detection performance based on direct and homogeneous antibody conjugation. After the linker-free PSF process, multiple particle rinsing steps are required to prevent unfavorable side reactions during the target capture step between unbound capture antibodies and target molecules, which can degrade the detection performance. This study investigates the importance of extent of dilution during particle rinsing after the linker-free PSF process on the sensitivity of encoded hydrogel microparticle-based immunoassay. First, the impact of dilution level in particle rinsing on signal intensity after immunoassay was characterized for four types of preeclampsia-related protein biomarkers. Consequently, the optimal dilution factor for particle rinsing was determined, and significantly enhanced sensitivity based on the optimized particle rinsing was realized. In addition, the robust specificity and spike recovery of the optimized rinsing process during the multiplex detection were validated.